The Impact of Cultural Dimensions on Islamic Students’ Attitude Towards Problem-Based Learning - Esti Zaduqisti (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2016)
The current study aims to examine the impact of cultural dimensions (i.e., collectivism, power distance, uncertainty avoidance, and masculinity) on students’ attitude towards problem-based learning. The design of the current study was a correlational survey, wherein participants were recruited by means of a convenient sampling. Inspection of a multiple regression analysis (N = 549) revealed that collectivism and masculinity positively corresponded with the attitudes. In particular, we found that that the higher the level of collectivism and masculinity, the more students supported the implementation of problem-based learning. In contrast, uncertainty avoidance was negatively related to the attitude in such a way that the higher this cultural dimension, the less students supported problem-based learning. Power distance was the only predictor that did not significantly predict students’ attitude towards problem-based learning. These findings overall suggest the importance of taking into account the characteristics of norms and values people hold within a country that might contribute to the success, feasibility, and suitability of problem-based learning. Theoretical implications and study limitations of the current findings are discussed, as are practical strategies highlighting on how to deal with cultural potentials and pitfalls in an attempt to promote problem-based learning.